Local Food Crops and the Poor (The Case of the Three Geographical Regions of Kulon Progo Regency) - Dodi Widiyanto; R. Rijanta; Toekidjo Toekidjo (The Indonesian Journal of Planning and Development, 2014)
It is believed that local food crops are available widely in rural regions. However, not all of the people consume them. The facts also show that local food crops are placed as secondary sources of foodstuff. This research aims at (1) describing the profile of local food crops consumed by the poor rural households and 2) exploring causes and mechanism of the poor rural household in maintaining local food crops as their food sources in the three different geographical regions of Kulon Progo Regency, namely the upland region, the transitional region, and the lowland region of Kulon Progo Regency. A household survey is conducted to achieve the above mentioned objectives. Respondents of this research arechosen purposively from the poor households’ data as listed by the Kulon Progo Regional Planning Board to represent the three regions in the regency. Three districts in the regency are selected to represent the three types of regions respectively, i.e: Samigaluh, Pengasih, and Lendah. A questionnaire is distributed in order to collect the data from the selectedhousehold respondents. The findings of this research are (1) there are various kinds of local food crops that were consumed by the respondents from three different geographical regions. The researchers collected that there were 36 types of local food totally from these three geographical regions, (2) there were also several motives that were important to be described in order to explained the reason why the respondents processed local food crops such as to be sold or to be consumed by themselves, (3) spatially, there are a specific pattern of harvested local food crops based on the respondents perceptions in three geographical areas: (i) based on nature, and (ii) based on human decision , (4) there were also various methods of utilisation local food crops, such as boiled, fried, steamed,  cooked into intermediate products, or cooked into final commodities that were ready to be consumed.